Continuity and Change in the Alum Industry: A Technological Approach to Wenzhou Alum Mine (Zhejiang Province, China, 14th-21st Century). (2nd July 2020) - Feng, Shujing; Qian, Wei; Cano Sanchiz, Juan Manuel; White, Roger; Robinson, Mike
ABSTRACT: Wenzhou Alum Mine in Fanshan Town, Zhejiang Province (China), operated from the middle of the 14th century to December 2017 and, as an important centre of the Chinese alum industry for more than 600 years, witnessed both change and continuity in the development of alum mining and refining technology. Alum was produced in Wenzhou from the alunite ore mined in the territory, and included quarrying, calcining, weathering and steeping the ore to produce an impure solution, or liquor, of aluminium sulphate and potassium sulphate, which was then boiled at the appropriate temperature to form a concentration of alum. A review of the documentary evidence coupled with an archaeological survey of the mining and refining sites owned by the Wenzhou Alum Mine Company has enabled the site to be redefined as a complex production landscape by paying attention to the evidence for the evolution of technology used for producing alum.